Calcium sources compared in liquid feed supplements for finishing steers - L.H. Harbers; R.D. Teague; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1975)
When calcium chloride was added to a mixture of minerals and urea in molasses, the minerals had not settled after the mixture was shipped 350 miles and stored 4 weeks. Calcium carbonate added to a similar supplement caused all minerals tested except sodium, potassium, and copper to precipitate. Using a 112-day, steer-feeding trial, we found that animals performed similarly when their liquid feed supplement contained either calcium chloride or resuspended calcium carbonate.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Calcium carbonate; Finishing steers; Calcium chloride